The vocational counselling role : perceptions of secondary school students : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Applied Psychology - Brook, Judith Anne (Massey University, 1977)
A Repertory test was constructed to determine the perceptions of 143 schoolchildren concerning people who gave them vocational counselling. A preliminary study elicited the constructs which they used to structure and order their interpersonal world. Each subject completed a version of the Repertory Grid consisting of 22 Role Titles and 22 supplied constructs. Grid responses were averaged and examined for the group as a whole as well as for sub-groups consisting of male and female, private and state school pupils, separately. The pattern of relationships existing between all 22 Role Figures was determined by subjecting the data to both a multidimensional scaling and an hierarchical clustering form of analysis. Clusters of figures produced by these methods were examined and discussed in terms of their composition and the descriptive adjectives and phrases associated with them. As predicted, it was found that the subjects made their discriminations between people on two major construct dimensions, an intimacy and a potency factor and that the vocational counselling persons appeared in two of the generalized figure clusters indicating that there are at least two distinct parts to the vocational counselling role. Different attributes in the counsellor are required for each of these different role functions. The composition and characteristics of other generalized figure clusters were also examined. The 18 subjects who were unable to complete their grids were considered as a separate group. For all subjects their relative standing in their school classes on the last set of examinations was taken as a measure of intellectual capacity but there was no evidence that a relationship existed between this and the ability of subjects to complete the grid protocols. Finally a number of possible extensions and refinements to the experiment were considered and an evaluation was made of the Repertory Grid technique as it was used in the present context.
Keywords: Vocational guidance; Vocational counselling; Vocational guidance counselling; Secondary school vocational counselling